Does family firm have better performance? empirical research in indonesia smes - Ratna Purnama Sari; Shinta Suryaningrum; Dekeng Setyo Budiarto (Faculty of Economics and Business Mulawarman University, 2019)
Small and Medium Enterprises (SMEs) have an essential and strategic role in national economic development. SMEs are proven to be resistant to the financial crisis and absorb part of the workforce in Indonesia. This study examines whether SMEs family firm and diversification have better performance. The research sample was 114 SMEs owners in the Special Region of Yogyakarta. The results of the study prove that SMEs family firm and SMEs that diversify have better performance. The results of this study are expected to provide advice to SMEs owners that family businesses can be expanded through diversification to increase business value.